ANALISIS KUALITAS PELAYANAN BADAN KEPEGAWAIAN DAN DIKLAT KABUPATEN LAMPUNG SELATAN - Eka Ubaya Ubaya; Nita Sulistiana (Universitas Bandar Lampung (UBL), 2023)
The Staffing and Training Agency of South Lampung Regency is one of the local government organizations providing staffing services in general. These services are aimed at serving employees and a small part of the community who need information related to staffing and training. Therefore, it is necessary to conduct research to find out how the quality of service provided by this agency affects service recipients. Analyzed with gap analysis, satisfaction level analysis, and importance-performance analysis, this study describes service quality in terms of five dimensions, namely physical evidence reliability, responsiveness, assurance, and empathy. The results of the importance-performance analysis show that there are six indicators that fall into Quadrant A to be concentrated on improving services, nine indicators in Quadrant B, four indicators in Quadrant C, and four indicators in Quadrant D. The quality of service of the South Lampung Regency Civil Service and Training Agency is seen from the five dimensions: the empathy dimension of the service agency has the highest level of satisfaction, namely 95.28%, and the physical display dimension has the lowest level of satisfaction, namely 80.63%. In a row from the highest level of satisfaction to the lowest level of satisfaction, namely the dimensions of empathy, responsiveness, assurance, reliability, and physical appearance.